Bulls, Bears, Boers and Brits : Finance and the Coming of War in Southern Africa, 1894-1899 - Phimister, Ian, (Afrika-Studiecentrum Series ;, 2025)
In the 1890s financial speculation and market manipulation were prominent features of the Southern African gold mining industry. Extravagantly capitalised, starved of working capital, and poorly managed, many mines could not be made to pay. Investors suffered more at the hands of Randlords than they did than they did from those of the Boer Government in Pretoria. By failing to take any of this into serious consideration, accounts that focus on mining company complaints as the root cause of the Jameson Raid and the outbreak of war in 1899 are missing a key dimension of the past.